(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
The governments that emerged from the Mexican Revolution extended regenerative speeches aimed at the creation of a new man. A project that had in the enterprising men and active young men their desired architects to transform the country, provided that they managed to highlight their virile characteristics in front of other men, their counterpart, distinguished by physical weakness and passivity. Chiapas was no stranger to those discourses where the masculine ideal, desired normative, is exemplified with the intention of disciplining the body through measures considered regenerative such as education, work and physical activity.